Stand Out the groundbreaking new strengths assessment from the leader of the strengths revolution - Buckingham, Marcus (Nashville, Tenn. Thomas Nelson, 2011)
Stand Out, the revolutionary new book and online assessment tool from Marcus Buckingham, is the result of extensive research, statistical testing, and analysis of the world's top performers. From the coauthor of Now, Discover Your Strengths and the recognized leader of the strengths movement, Stand Out unveils your top two Strength Roles and offers sharp, practical ideas that professionals and managers in any organization can use to find their edge and win at work.
Includes bibliographical references and index.
Keywords: Creative ability in business